Closing the Digital Divide: Strategies for Addressing Inequalities in Technology Access in Higher Education Institutions - Dyantyi, Ntsika; Mkabile-Masebe, Bulelwa (Research in Social Sciences and Technology- OpenED Network, 2025)
Institutions of higher learning in the Eastern Cape face significant challenges in ensuring equitable access to technology among their student population. The digital divide, exacerbated by socioeconomic disparities, poses a barrier to academic success and hinders the realization of educational goals. This paper explores strategies for addressing inequalities in technology access within higher education institutions, drawing insights from empirical research conducted in an institution of higher learning within the Eastern Cape. Semi-structured interviews were employed as the data collection instrument, involving six participants comprising both lecturers and students. The collected data were analysed utilising the thematic approach. The findings revealed that to close the digital divide, the university should invest in infrastructure development, benchmark with other universities, and provide training programs to both lecturers and students. Hence, the study recommended that the university collaborate with government agencies, non-profit organisations, and industry partners, to leverage resources and expertise to address socioeconomic barriers to technology access. The university should also ensure that all initiatives and interventions are designed with a focus on equity and inclusion, considering students’ diverse needs and backgrounds.